2020
DOI: 10.1101/2020.10.08.331405
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Synonymous mutations reveal genome-wide driver mutation rates in healthy tissues

Abstract: Genetic alterations that drive clonal expansions in ostensibly healthy tissues have implications for cancer risk. However, the total rate at which clonal expansions occur in healthy tissues remains unknown. Synonymous passenger mutations that hitchhike to high variant allele frequency due to a linked driver mutation can be used to estimate the total rate of positive selection across the genome. Because these synonymous hitchhikers are influenced by all mutations under selection, regardless of type or location,… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 50 publications
0
8
0
Order By: Relevance
“…concluded that there must be hidden driver mutations to explain the allele frequency distribution of synonymous mutations. 63 In conclusion, current evidence points to a role for natural selection in clonal hematopoiesis but more evidence is needed before ruling out a role of neutral evolution.…”
Section: Is the Number Of Contributing Hscs Compatible With Genetic Dmentioning
confidence: 93%
See 1 more Smart Citation
“…concluded that there must be hidden driver mutations to explain the allele frequency distribution of synonymous mutations. 63 In conclusion, current evidence points to a role for natural selection in clonal hematopoiesis but more evidence is needed before ruling out a role of neutral evolution.…”
Section: Is the Number Of Contributing Hscs Compatible With Genetic Dmentioning
confidence: 93%
“…10% of myeloproliferative neoplasms, 95,96 although it is always possible that genetic or epigenetic driver alterations have been undetected. 63 In addition, genetic drift could explain growth of clones with mutations providing no clear fitness advantage to stem cells such as JAK2 V617F , 97 or SRSF2 P95H mutations, 98 The final column states the impact of the mutation as predicted by 21 . D indicates that the mutation is predicted to be damaging and N that the mutation is predicted to be neutral.…”
Section: Conclusion and Perspectivementioning
confidence: 99%
“…The mutational events that drive CH overlap with known drivers of hematologic malignancies. However, the majority of mutations in CH appear to occur outside of canonical cancer driver genes 11,12 . The impact of individual mutational events on hematopoietic stem and progenitor cells differs by the nature of the genomic aberration.…”
Section: Mainmentioning
confidence: 99%
“…As such, the observed events that are highly enriched in CH could be 'passenger' mutations that co-occur with a positively selected, undetected 'driver' mutation such as recurrent CNVs. 12,13 Alternatively, driver mutations may have been incompletely classified as "non-driver" events using our methodology. However, cancer driver genes tend to recur in multiple patients, and the majority of witnessed non-driver mutated genes in our cohort were non-recurrent suggesting that clonal expansion, and not the specific event driving clonal expansion, may be associated with Covid-19 disease severity.…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation